Heresy, Doubt and Identity: Late Medieval Friars in the Kingdom of Aragon - Graham, Emily E. (Studies in church history, 2016)
The fourteenth-century Kingdom of Aragon enjoyed a reputation as a haven for religious dissidents, doubters, heretical refugees and malcontents. This is particularly true of those fleeing the upheaval that the Franciscan Order experienced early in the century, as debates over the nature of poverty within the order created serious conflicts within communities, between friars and superiors, and between the order and the papacy. These visitors operated at the highest levels of the royal court, as has been well documented in the recent surge of interest in figures such as Ramon Llull and Arnald of Villanova. But the effects were also felt in rural communities, arousing suspicion among local bishops. Court proceedings and other documents reveal the pervasive atmosphere of doubt and suspicion that focused on several Franciscan houses in the diocese of Barcelona as late as the middle of the fourteenth century.